Heat treatment method for improving structure uniformity of additive-state GH4169 alloy

Through pre-aging treatment, homogenization treatment and dual-stage aging treatment, the problems of microstructure anisotropy and inhomogeneity of the additive state GH4169 alloy are solved, and its mechanical properties are significantly improved.

CN119464987APending Publication Date: 2025-02-18HUAZHONG UNIV OF SCI & TECH

Patent Information

Application Number
CN202411626269.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-10-23
Filing Date
2024-11-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The microstructure of the additive state GH4169 alloy has significant anisotropy and inhomogeneity, which affects its mechanical properties. The existing standard heat treatment processes cannot effectively regulate the grain structure, resulting in limited mechanical properties.

Method used

The heat treatment method is adopted for pre-aging treatment, homogenization treatment and dual-stage treatment. In the pre-aging treatment, the delta phase is precipitated at the columnar crystal grain boundaries, the Laves phase is dissolved in the homogenization treatment and the diffusion of Nb elements is promoted. In the two-stage aging treatment, the γ' phase and the γ" phase are uniformly distributed.

Benefits of technology

It effectively limits grain growth, dissolves the Laves phase that is unfavorable to mechanical properties, promotes the uniform precipitation of γ' phase and γ' phase, transforms the grain structure, and significantly improves the mechanical properties of the additive state GH4169 alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464987A_ABST
    Figure CN119464987A_ABST
Patent Text Reader

Abstract

The invention discloses a heat treatment method for improving the structure uniformity of an additive-state GH4169 alloy, and belongs to the technical field of heat treatment processes. The method comprises the following steps: carrying out pre-aging treatment on the additive-state GH4169 alloy, and carrying out air cooling to room temperature; then carrying out homogenization treatment, and carrying out water cooling to room temperature; and finally, two-stage aging treatment is conducted, and air cooling is conducted to the room temperature. According to the method, the delta phase is precipitated at the grain boundary in a saturated mode through pre-aging treatment, and grain growth in the follow-up homogenization process is effectively limited through pinning of the grain boundary; the precipitation uniformity of a gamma'phase and a gamma ''phase in subsequent two-stage aging treatment is improved through homogenization treatment, recrystallization can be promoted, the grain structure can be transformed, the texture strength can be reduced, the grain structure uniformity can be improved, and the mechanical property of the additive-state GH4169 alloy can be improved; two-stage aging treatment is adopted, so that a gamma'phase and a gamma ''phase which are uniformly distributed are separated out from the additive-state GH4169 alloy, the effect of aging strengthening is achieved, and the yield strength, the tensile strength, the ductility and other mechanical properties of the additive-state GH4169 alloy are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heat treatment processes, and in particular relates to a heat treatment method for improving the uniformity of the microstructure of an additively treated GH4169 alloy. Background Art

[0002] Nickel-based superalloys are widely used in key hot-end components of high-end equipment such as aircraft engines and gas turbines due to their excellent high-temperature strength, good corrosion resistance and oxidation resistance. However, due to the high deformation resistance and narrow processing window of superalloys, the manufacturing and forming of complex components are difficult. In recent years, additively manufactured nickel-based superalloys have attracted widespread attention from the aviation and aerospace industries due to their advantages of rapid prototyping and high degrees of freedom. Among them, GH4169 alloy is highly favored in additively manufactured nickel-based superalloys due to its excellent welding performance. The matrix of GH4169 alloy is mainly composed of γ face-centered cubic phase. In the additive state and after heat treatment, a variety of second phases can be observed in the matrix, including Laves phase, δ phase, γ' strengthening phase, γ” strengthening phase, metal carbides and metal nitrides.

[0003] In the additive manufacturing process of GH4169 alloy, layer-by-layer deposition leads to uneven temperature gradients and rapid solidification rates, resulting in columnar crystal structures. Due to the preferred orientation of the growth direction of columnar crystals and the generally large grain size, mechanical properties such as tensile strength, creep resistance and ductility show anisotropy. In addition, the segregation of alloying elements such as Nb, Ti, and Mo leads to the precipitation of interdendritic Laves phases, metal carbides, and metal nitrides. Laves phases are generally not conducive to tensile properties, high-cycle fatigue life, and corrosion resistance. Therefore, the microstructure of the additive GH4169 alloy has significant anisotropy and inhomogeneity, which affects its mechanical properties and, in turn, its subsequent forming and application. In order to regulate the microstructure of the additive GH4169 alloy, a heat treatment process is usually used. However, the main purpose of the standard heat treatment process (GB / T 40313-2021) is to precipitate the strengthening phase, which cannot effectively regulate the grain structure of the additive GH4169 alloy and reduce the anisotropy and inhomogeneity of the microstructure, which seriously affects the mechanical properties of the additive GH4169 alloy components. Therefore, it is urgent to develop a new heat treatment method to improve the uniformity of the microstructure of the additive GH4169 alloy, so as to overcome the above problems. Summary of the invention

[0004] Based on the above reasons, in view of the problems or defects existing in the prior art, the purpose of the present invention is to provide a heat treatment method for improving the uniformity of the microstructure of the additively treated GH4169 alloy, so as to solve or at least partially solve the above technical defects existing in the prior art.

[0005] The present invention is achieved by a heat treatment method for improving the uniformity of the microstructure of the additively treated GH4169 alloy, comprising the following steps:

[0006] The additively treated GH4169 alloy was pre-aged and then air-cooled to room temperature; then homogenized and water-cooled to room temperature; finally, a double-stage aging treatment was performed and air-cooled to room temperature.

[0007] Furthermore, in the above technical solution, the treatment temperature in the pre-aging treatment is 800-1000°C.

[0008] Furthermore, in the above technical solution, the treatment time in the pre-aging treatment is 0.5 to 48 hours.

[0009] Specifically, in the above technical solution, the pre-aging treatment can precipitate a large amount of δ phase in the additive GH4169 alloy, which plays a role in pinning grain boundaries and limiting grain boundary migration. The purpose of air cooling after the pre-aging treatment is to reduce the temperature to room temperature and precipitate more δ phase during the cooling process.

[0010] Furthermore, in the above technical solution, the processing temperature in the homogenization treatment is 1100-1250°C.

[0011] Furthermore, in the above technical solution, the processing time in the homogenization treatment is 0.5 to 4 hours.

[0012] Specifically, in the above technical solution, the homogenization treatment can dissolve the Laves phase in the additive GH4169 alloy, promote the diffusion of the Nb element, and improve the uniformity of the Nb element, thereby improving the precipitation uniformity of the γ' phase and the γ" phase in the subsequent two-stage aging treatment, which is beneficial to enhancing the mechanical properties. In addition, since the temperature at which the GH4169 alloy begins to recrystallize is 1100°C, the homogenization treatment can promote the occurrence of recrystallization, so that the additive GH4169 alloy is transformed from a grain structure dominated by columnar crystals to a grain structure composed of equiaxed crystals and twins, while reducing the texture strength, randomizing the texture orientation, improving the uniformity of the grain structure, and weakening the anisotropy. The purpose of water cooling after the homogenization treatment is to reduce the temperature to room temperature and avoid the precipitation of the second phase of impurities during the cooling process.

[0013] Furthermore, in the above technical solution, the treatment temperature of the first stage in the double-stage aging treatment is 720°C.

[0014] Furthermore, in the above technical solution, the treatment time of the first stage in the double-stage aging treatment is 8 hours.

[0015] Furthermore, in the above technical solution, the treatment temperature of the second stage in the double-stage aging treatment is 620°C.

[0016] Furthermore, in the above technical solution, the treatment time of the second stage in the double-stage aging treatment is 8 hours.

[0017] Specifically, in the above technical solution, the two-stage aging treatment can precipitate uniformly distributed γ' phase and γ" phase in the additive GH4169 alloy, which plays a role of aging strengthening and is beneficial to improving the mechanical properties such as yield strength, tensile strength and elongation of the additive GH4169 alloy. The purpose of air cooling after pre-aging treatment is to reduce the temperature to room temperature and precipitate more γ' phase and γ" phase during the cooling process.

[0018] In view of the technical problems existing in the above-mentioned prior art and the difficulty in solving the problems, some creative technical effects are brought about after solving the problems. The specific description is as follows:

[0019] During the layer-by-layer deposition of the GH4169 alloy, the uniform temperature gradient and the rapid solidification rate usually lead to the generation of columnar crystal structure. Since the growth direction of the columnar crystal is parallel to the direction of the temperature gradient, the alloy microstructure has significant anisotropy, resulting in anisotropy in mechanical properties such as tensile properties, creep resistance and ductility. In addition, the segregation of alloying elements such as Nb, Ti, and Mo leads to the precipitation of Laves phase between dendrites. Laves phase is usually not conducive to tensile properties, high-cycle fatigue life and corrosion resistance. Therefore, the microstructure of the additive GH4169 alloy has significant anisotropy and inhomogeneity, which affects its subsequent forming and application. However, the standard heat treatment process cannot effectively regulate the grain structure of the additive GH4169 alloy, reduce the anisotropy and inhomogeneity of the microstructure, and seriously affect the mechanical properties of the additive GH4169 alloy components. The present invention adopts a heat treatment method of pre-aging treatment, homogenization treatment and double-stage aging treatment to improve the uniformity of the organization of the additive GH4169 alloy. The present invention adopts pre-aging treatment to saturate the precipitation of δ phase at the grain boundary of columnar crystals, which plays the role of pinning grain boundaries and limiting grain boundary migration, and can effectively limit the growth of grains in the subsequent homogenization process. The present invention adopts homogenization treatment to dissolve Laves phase, promote the diffusion of Nb element, improve the uniformity of Nb element, thereby improving the precipitation uniformity of γ' phase and γ" phase in the subsequent double-stage aging treatment; the homogenization treatment can promote the occurrence of recrystallization, so that the grain structure is transformed from the grain structure dominated by columnar crystals to the grain structure composed of equiaxed crystals and twins, reduce the texture strength, randomize the texture orientation, improve the uniformity of the grain structure, significantly weaken the anisotropy of the microstructure, and improve the mechanical properties of the additive GH4169 alloy. The present invention adopts double-stage aging treatment to precipitate uniformly distributed γ' phase and γ" phase in the additive GH4169 alloy, which plays the role of aging strengthening, which is beneficial to improve the mechanical properties of the additive GH4169 alloy such as yield strength, tensile strength and elongation. The technical solution of the present invention provides a new process path in the field of heat treatment of additively processed alloys, and also has important reference value and application potential for the heat treatment of other additively processed alloy materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 It is a schematic flow chart of a heat treatment method for improving the uniformity of the microstructure of the additively treated GH4169 alloy according to the present invention;

[0022] Figure 2 is the inverse pole figure of the additively treated GH4169 alloy sample in Comparative Example 1 of the present invention;

[0023] Figure 3 is the pole figure of the {001} crystal plane of the additively treated GH4169 alloy sample in Comparative Example 1 of the present invention;

[0024] Figure 4 is an electron microscope image of the additively treated GH4169 alloy sample in Comparative Example 1 of the present invention;

[0025] Figure 5 is the inverse pole figure of the additively treated GH4169 alloy sample after homogenization in Example 1 of the present invention;

[0026] Figure 6 is the pole figure of the {001} crystal plane of the additively treated GH4169 alloy sample after homogenization in Example 1 of the present invention;

[0027] Figure 7 is the inverse pole figure of the additively treated GH4169 alloy sample after homogenization in Example 2 of the present invention;

[0028] Figure 8 It is the pole figure of the {001} crystal plane of the additively treated GH4169 alloy sample after homogenization in Example 2 of the present invention.

[0029] Fig. 9 is a strengthening phase distribution diagram of the additively treated GH4169 alloy sample in Example 2 of the present invention;

[0030] Fig.10 is the inverse pole figure of the additively treated GH4169 alloy sample after homogenization in Comparative Example 2 of the present invention;

[0031] Fig.11 is a pole figure of the {001} crystal plane of the additively treated GH4169 alloy sample after homogenization in Comparative Example 2 of the present invention;

[0032] Fig.12 is the inverse pole figure of the additively treated GH4169 alloy sample after homogenization in Comparative Example 3 of the present invention;

[0033] Fig.13 It is the pole figure of the {001} crystal plane of the additively treated GH4169 alloy sample after homogenization in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0034] The present invention discloses a heat treatment method for improving the uniformity of the microstructure of an additively-made GH4169 alloy. The method of the present invention specifically comprises the following steps: pre-aging the additively-made GH4169 alloy, and then air-cooling it to room temperature; then performing a homogenization treatment, and water-cooling it to room temperature; and finally performing a double-stage aging treatment, and air-cooling it to room temperature. The present invention adopts a pre-aging treatment to saturately precipitate a δ phase at the grain boundary of the columnar crystal, which plays a role in pinning the grain boundary and limiting the migration of the grain boundary, and can effectively limit the growth of grains in the subsequent homogenization process. The present invention adopts homogenization treatment to dissolve the Laves phase, promote the diffusion of Nb element, improve the uniformity of Nb element, thereby improving the precipitation uniformity of γ' phase and γ" phase in the subsequent two-stage aging treatment; the homogenization treatment can promote the occurrence of recrystallization, so that the grain structure is transformed from the grain structure dominated by columnar crystals to the grain structure composed of equiaxed crystals and twins, reduce the texture strength, randomize the texture orientation, improve the uniformity of the grain structure, significantly weaken the anisotropy of the microstructure, and improve the mechanical properties of the additive GH4169 alloy. The present invention adopts two-stage aging treatment to precipitate uniformly distributed γ' phase and γ" phase in the additive GH4169 alloy, which plays a role of aging strengthening, and is beneficial to improve the mechanical properties of the additive GH4169 alloy such as yield strength, tensile strength and elongation.

[0035] The present invention is further described in detail below through implementation cases.

[0036] The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0037] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0038] Comparative Example 1

[0039] In this comparative example, additive GH4169 alloy samples were prepared: the substrate was made of forged GH4169 alloy, the main chemical components were: Ni 52.91%, Cr 19.01%, Nb 4.75%, Mo 2.80%, Al 0.20%, Ti 0.97%, C 0.05%, Si 0.10%, and the balance was Fe, where the unit of chemical composition was wt.%. The wire was made of GH4169 welding wire with a diameter of 1.1 mm, the main chemical components were: Ni 52.91%, Cr 19.01%, Nb 4.75%, Mo 2.80%, Al 0.20%, Ti 0.97%, C 0.05%, Si 0.10%, and the balance was Fe, where the unit of chemical composition was wt.%. The additive process adopts cold metal transition process, the additive current is 120A, the additive voltage is 18V, the wire feeding speed is 4.8m / min, the additive speed is 0.5m / min, the protective gas adopts argon atmosphere, the gas flow rate is 20L / min; the interlayer cooling time is 3min.

[0040] Specifically, according to Figure 2 The inverse pole figure of the additively treated GH4169 alloy sample is shown. The grain structure is dominated by columnar crystals, and the growth direction of the columnar crystals is along the bottom-up construction direction. Figure 3 The pole figure of the {001} crystal plane of the additively treated GH4169 alloy sample is shown. The pole clusters diffuse along the deposition direction. The pole clusters are concentrated in the construction direction. The grain structure shows a strong {001} <100> Rotated cubic texture, texture strength is 14.683MRD. Figure 4 The electron microscope image of the additively treated GH4169 alloy sample shows that the chain-like Laves phase is mainly distributed in the interdendritic region. These indicate that the microstructure of the additively treated GH4169 alloy has significant anisotropy and inhomogeneity.

[0041] Example 1

[0042] The embodiment of the present invention provides a heat treatment method for improving the microstructure uniformity of the additively treated GH4169 alloy, comprising the following steps:

[0043] (1) Preparation of additively processed GH4169 alloy specimens

[0044] The substrate is made of forged GH4169 alloy, with the main chemical composition of Ni52.91%, Cr19.01%, Nb4.75%, Mo2.80%, Al0.20%, Ti0.97%, C0.05%, Si0.10%, and the balance is Fe, where the unit of chemical composition is wt.%. The wire is GH4169 welding wire with a diameter of 1.1 mm, with the main chemical composition of Ni52.91%, Cr19.01%, Nb4.75%, Mo2.80%, Al0.20%, Ti0.97%, C0.05%, Si0.10%, and the balance is Fe, where the unit of chemical composition is wt.%. The additive process adopts cold metal transition process, with additive current of 120A, additive voltage of 18V, wire feeding speed of 4.8m / min, additive speed of 0.5m / min, argon atmosphere as protective gas, and gas flow rate of 20L / min; interlayer cooling time is 3min.

[0045] (2) Heat treatment

[0046] First, a pre-aging treatment was performed. The additively treated GH4169 alloy sample prepared in step (1) was heated to 900°C at a heating rate of 10°C / min, kept at that temperature for 12 h, and then air-cooled to room temperature.

[0047] Then, a homogenization treatment was performed: the pre-aging treated sample was heated to 1150°C at a heating rate of 10°C / min, kept at that temperature for 1h, and then water-cooled to room temperature.

[0048] Finally, a double-stage aging treatment was carried out: the homogenized sample was heated to 720°C at a heating rate of 10°C / min and kept at that temperature for 8 h, furnace cooled to 620°C and kept at that temperature for 8 h, and then air cooled to room temperature.

[0049] Specifically, according to Figure 5 The inverse pole figure of the additively treated GH4169 alloy sample after homogenization is shown in Figure 2. Figure 2 , the grain structure changes from a grain structure dominated by columnar crystals to a grain structure composed of equiaxed crystals, twins and a small amount of columnar crystals. Figure 6 The pole figure of the {001} crystal plane of the additively treated GH4169 alloy sample after homogenization is shown in Figure 2. Figure 3 , the extreme point cluster along the construction direction moves downward, and the texture strength is reduced to 9.256MRD. It can be shown that the present invention can achieve the transformation of grain structure and the reduction of texture strength by promoting the occurrence of recrystallization, improve the uniformity of grain structure, and significantly weaken the anisotropy of microstructure.

[0050] Example 2

[0051] The embodiment of the present invention provides a heat treatment method for improving the microstructure uniformity of the additively treated GH4169 alloy, comprising the following steps:

[0052] (1) Preparation of additively treated GH4169 alloy specimens

[0053] The substrate is made of forged GH4169 alloy, with the main chemical composition of Ni52.91%, Cr19.01%, Nb4.75%, Mo2.80%, Al0.20%, Ti0.97%, C0.05%, Si0.10%, and the balance is Fe, where the unit of chemical composition is wt.%. The wire is GH4169 welding wire with a diameter of 1.1 mm, with the main chemical composition of Ni52.91%, Cr19.01%, Nb4.75%, Mo2.80%, Al0.20%, Ti0.97%, C0.05%, Si0.10%, and the balance is Fe, where the unit of chemical composition is wt.%. The additive process adopts cold metal transition process, with additive current of 120A, additive voltage of 18V, wire feeding speed of 4.8m / min, additive speed of 0.5m / min, argon atmosphere as protective gas, and gas flow rate of 20L / min; interlayer cooling time is 3min.

[0054] (2) Heat treatment

[0055] First, a pre-aging treatment was performed. The additively treated GH4169 alloy sample prepared in step (1) was heated to 900°C at a heating rate of 10°C / min, kept at that temperature for 12 h, and then air-cooled to room temperature.

[0056] Then, a homogenization treatment was performed: the pre-aging treated sample was heated to 1100°C at a heating rate of 10°C / min, kept at that temperature for 1h, and then water-cooled to room temperature.

[0057] Finally, a double-stage aging treatment was carried out: the homogenized sample was heated to 720°C at a heating rate of 10°C / min and kept at that temperature for 8 h, furnace cooled to 620°C and kept at that temperature for 8 h, and then air cooled to room temperature.

[0058] Specifically, according to Figure 7 The inverse pole figure of the additively treated GH4169 alloy sample after homogenization is shown in Figure 2. Figure 2 , the grain structure changes from a grain structure dominated by columnar crystals to a grain structure composed of equiaxed crystals and twins. Figure 8 The pole figure of the {001} crystal plane of the additively treated GH4169 alloy sample after homogenization is shown in Figure 2. Figure 3, the distribution of the poles is randomized, and the texture strength is reduced to 8.694MRD. It can be shown that the present invention can achieve the transformation of grain structure, the reduction of texture strength and the randomization of texture orientation by promoting the occurrence of recrystallization, thereby improving the uniformity of grain structure and significantly weakening the anisotropy of microstructure. Fig. 9 From the strengthening phase distribution diagram of the additive GH4169 alloy sample after heat treatment, it can be seen that the γ' / γ" strengthening phase is uniformly distributed in the matrix, and its morphology is mainly spherical, with an average diameter of 450nm and an average diameter range of 60nm. Under the action of pre-aging treatment and homogenization treatment, the double-stage aging causes the uniformly distributed γ' / γ" strengthening phase to precipitate in the additive GH4169 alloy, which can have the effect of aging strengthening, and is beneficial to improve the mechanical properties of the additive GH4169 alloy such as yield strength, tensile strength and elongation.

[0059] Table 1 below is a comparison of the additive GH4169 alloy in Comparative Example 1, the additive GH4169 alloy after heat treatment in Example 2, and the standard mechanical properties of GH4169 alloy forgings (GB / T 40313-2021). The test method for high-temperature tensile properties adopts the high-temperature tensile test method in GB / T 228.2. It can be seen that the yield strength, tensile strength and elongation of the additive GH4169 alloy are lower than the standard mechanical properties of GH4169 alloy forgings, and there is obvious anisotropy in the mechanical properties in different directions. After the heat treatment of the present invention, the yield strength, tensile strength and elongation of the additive GH4169 alloy after heat treatment are significantly improved, which are better than the standard mechanical properties of GH4169 alloy forgings, and the mechanical properties in different directions are similar, and the anisotropy is eliminated.

[0060] Table 1 Mechanical properties of GH4169 alloy in different states

[0061]

[0062]

[0063] Comparative Example 2

[0064] The method described in this comparative example is basically the same as that of Examples 1 and 2, with the only difference being that in step (2) the heat treatment, the temperature of the homogenization treatment is 1000°C.

[0065] Specifically, according to Fig.10 The inverse pole figure of the additively treated GH4169 alloy sample after homogenization is shown in Figure 2. Figure 5 and Figure 7 , the grain structure is still mainly columnar. Fig.11 The pole figure of the {001} crystal plane of the additively treated GH4169 alloy sample after homogenization is shown in Figure 2. Figure 6 and Figure 8 , the grain structure still shows strong {001} <100> Rotated cubic texture, texture strength is 23.446 MRD. It can be explained that when the homogenization temperature is lower than the homogenization temperature range of the present invention, no recrystallization occurs, and the microstructure still maintains significant anisotropy and inhomogeneity.

[0066] Comparative Example 3

[0067] The method described in this comparative example is basically the same as that of Examples 1 and 2, with the only difference being that in step (2) heat treatment, the temperature of the homogenization treatment is 1050°C.

[0068] Specifically, according to Fig.12 The inverse pole figure of the additively treated GH4169 alloy sample after homogenization is shown in Figure 2. Figure 5 and Figure 7 , the grain structure is still mainly columnar. Fig.13 The pole figure of the {001} crystal plane of the additively treated GH4169 alloy sample after homogenization is shown in Figure 2. Figure 6 and Figure 8 , the grain structure still shows strong {001} <100> Rotated cubic texture, texture strength is 20.901 MRD. It can be explained that when the homogenization temperature is lower than the homogenization temperature range of the present invention, no recrystallization occurs, and the microstructure still maintains significant anisotropy and inhomogeneity.

[0069] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A heat treatment method for improving the uniformity of the microstructure of the additively treated GH4169 alloy, characterized in that: The following steps are involved: The additively treated GH4169 alloy was pre-aged and then air-cooled to room temperature; then homogenized and water-cooled to room temperature; finally, a double-stage aging treatment was performed and air-cooled to room temperature.

2. The heat treatment method according to claim 1, characterized in that: The treatment temperature in the pre-aging treatment is 800-1000°C.

3. The heat treatment method according to claim 1, characterized in that: The treatment time in the pre-aging treatment is 0.5 to 48 hours.

4. The heat treatment method according to claim 1, characterized in that: The treatment temperature in the homogenization treatment is 1100-1250°C.

5. The heat treatment method according to claim 1, characterized in that: The treatment time in the homogenization treatment is 0.5 to 4 hours.

6. The heat treatment method according to claim 1, characterized in that: The treatment temperature of the first stage of the two-stage aging treatment is 720°C.

7. The heat treatment method according to claim 1, characterized in that: The treatment time of the first stage in the double-stage aging treatment is 8 hours.

8. The heat treatment method according to claim 1, characterized in that: The treatment temperature of the second stage of the two-stage aging treatment is 620°C.

9. The heat treatment method according to claim 1, characterized in that: The treatment time of the second stage in the double-stage aging treatment is 8 hours.

Citation Information

Patent Citations

  • Heat treatment process method for selective laser melting forming GH4169

    CN112239838A

  • Pre-forging heat treatment method for nickel-based alloy arc fuse wire additive prefabricated part

    CN116200689A

Cited By

  • High-performance special alloy plate strip under high-Nb alloying design and preparation method of high-performance special alloy plate strip

    CN120505543A